Downton Abbey. Season 6 [videorecording (DVD)] - Fellowes, Julian (PBS Distribution, 2016)
The year is 1925. Momentous changes threaten the great house, its owners, and its servants, while past scandals continue to loom. Return to the sumptuous setting of Downton Abbey for the sixth and final season to discover what will finally become of the Crawley family, and the servants who work for them, as they face new challenges and begin forging different paths in a rapidly changing world. Secrets and rifts threaten the unity of the family, while those below stairs continue to navigate social changes which put their futures in jeopardy.